KEANEKARAGAMAN JENIS MAKROFAUNA TANAH PADA LAHAN BUDIDAYA KENTANG ORGANIK DI DESA CANDIKUNING KABUPATEN TABANAN SEBAGAI SUMBER PEMBELAJARAN BIOLOGI - I Gusti Ayu Rai; Yuniari Suryatini Kadek; Subrata I Made; Riska Yundari Ni Luh; Budiyasa I Wayan (Emasains : Jurnal Edukasi Matematika dan Sains, 2020)
Soil macrofauna is part of soil biodiversity that plays a roleimportant in improving the physical, chemical, and biological properties of soil. Soil macrofauna has an important role in the decomposition of soil organic matter in providing nutrients. Macrofauna will break up the dead vegetable substances, then the material will be excreted in the form of feces.This study aims to determine the diversity of soil macrofauna types in organic potato cultivation land in Candikuning Village, Tabanan Regency. Data were collected by direct observation method using quadratic tools. Data in the form of soil macrofauna diversity were analyzed using the Shannon Wienner diversity index. Based on the results of data analysis, it was found that the diversity index value (H ') was 3.103, belonging to the high diversity criteria (H'> 3). The results showed that the organic farming system can maintain the stability of the soil ecosystem due to the use of organic fertilizers and biopesticides in agricultural management. The results of this study can also be used as a source of learning biology in the application of the 2013 curriculum in class 10th of Senior High School, on the subject matter of Biodiversity and Animalia Kingdom.